Construction of Au@PB NPs doped graphene paper as flexible electrode for real-time monitoring of living cells and biosensing platform. (20th September 2021) - Zhang, Wenrui; Qin, Yanan; Wang, Weilan; Liu, Fujun; Meng, Fanxing; Chen, Fei; Zhu, Nan; Aihaiti, Aihemaitijiang; Zhang, Minwei
Abstract: In this work, we report a high-performance graphene flexible paper electrode composed of core-shell Gold@Prussian blue nanoparticles (Au@PB NPs) for real-time monitoring of living cell and biosensor platform. Core-shell Au@PB NPs with high stability, low cost, excellent biocompatibility and electrochemical activity was prepared. At the same time, combined with the robust mechanical properties of reduced graphene oxide (rGO) paper, an independent flexible graphene paper electrode was prepared and broadly characterized. Because of the unique structural properties and the combinational advantages of different components in the Au@PB NPs-rGO composite, the resultant nanohybrid paper electrode exhibits good electrochemical sensing performance toward hydrogen peroxide (H2 O2 ) and it also displays a very short response time (1 s) in the tracking of H2 O2 secretion by living HepG2 cells. Meanwhile, the as-prepared Au@PB NPs-rGO paper electrode can be further used as an enzyme-based biosensor. In this regard, glucose oxidase (GODx) used as an example for glucose detection and analysis, which proves its excellent performance as an enzyme sensing platform. The excellent properties of the kind of nanocomposites are expected to be further used in the field of flexible devices and Point-of-Care (POC).